Magnetite (Fe3O4) Nanoparticle Synthesis using Silica (SiO2) Template and Magnetic Properties Characterisation - Suryani Taib; Edi Suharyadi (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2015)
Nanoparticles of magnetite (Fe3O4) have been successfully synthesized by coprecipitation method by mixing FeSO4.7H2O and FeCl3.6H2O with the addition of 10% NH4OH as kopresipitan. Then, functionalized Fe3O4  concentration variation silica (SiO2) 5%, 10%, 15%, 20%, 30% and 50%. Particle size and magnetic properties of Fe3O4 nanoparticles were tested by X-Ray Diffraction (XRD) and Vibrating Sample Magnetometer (VSM). XRD results showed the addition of silica is not found new phases when added SiO2that serves as a template. The particle size of Fe3O4 nanoparticles obtained 14.23 nm, while the Fe3O4nanoparticles with the addition of a concentration of 5% and 20% respectively SiO215.45 nm and 16.37 nm. VSM results show the value of saturation magnetization and remanent magnetization decreased as more silica concentration, and increased coercivity field. Test Results of Fourier Transform Infra Red (FTIR) obtained new peaks which indicate that the functionalization process Fe3O4 with silica has been successfully carried out.